Politics of Education in Curriculum Development Policy in Indonesia from 1947 to 2013: A Documentary Research - Alhamuddin; Fanani, Ahmad; Yasin, Ilyas; Murniati, Andi (Jurnal Pendidikan Islam, 2020)
The dynamics of curriculum development in Indonesia from 1947 to the latest 2013 curriculum cannot be separated from political influence. This paper investigates the politics of educational policy in Indonesia’s curriculum development from 1947 to 2013, a critical analysis of various polemics about Indonesian education’s aims and contents in schools. This paper is documentary research, which refers to related previous documents or literature. The study results indicate that the development of Indonesia’s education curriculum is closely influenced by political, economic, social, cultural, and globalization factors. The formulated curriculum content cannot be separated from these factors’ influence, as the 2013 curriculum was recently implemented. Of all these factors, government interests and political paradigms have the most significant influence in changing, developing, and refining the curriculum from time to time. The 2013 curriculum policy is intended to improve the various deficiencies that existed in the previous curriculum. The 2013 curriculum is structured by developing and strengthening attitudes, knowledge, and skills in a balanced manner. This research’s implication is hoped that policymakers can consider it in developing curriculum in Indonesia.